Optimizing E-Posyandu Through Digitalization of the Poedji Rochjati Score Card (KSPR) in Detecting the Risk of Maternal - Ervina Rachmawati; Maya Weka Santi; Trismayanti Dwi Puspitasari; Yohan Yuanta (P3M Politeknik Negeri Jember, 2026)
Jember Regency has a high maternal mortality rate (MMR) in East Java Province. Meanwhile, Arjasa Village, Jember is a partner village of Jember State Polytechnic which has the same health problem. In previous research, the e-posyandu application had not developed a system that could detect high-risk pregnant women. The purpose of this study was to optimize E-Posyandu through the Digitalization of the Poedji Rochjati Score Card (KSPR) in Detecting the Risk of Maternal in Arjasa, Jember. Methods: This was a research and development study. The sample were 15 cadres from integrated service posts in Arjasa village. The system was developed using the waterfall method. The results showed that the system’s development of e-Posyandu through the digitalization of the Poedji Rochjati Score Card (KSPR) is able to detect early high-risk pregnant women with three categories: low-risk pregnancy (KRR), high-risk pregnancy (KRT) and very high-risk pregnancy (KRST). High-risk and very high-risk pregnant women are then reported to the village midwife and the Community Health Center to get a referral to the hospital to prevent maternal mortality. Conclusion: This system has been tested with a system accuracy result of 93%, response time of <10 seconds, and user satisfaction with this system reached 87%, so it can increase the efficiency of cadres and midwives in reporting the results of early detection of high-risk pregnant women in real time to the Community Health Center. Recommendation: improve the system by shortening response time, increasing user satisfaction and increase sample size all Posyandu in Jember Regency for future research.